Effects of thermal treatment on acoustic waves in Carrara marble. (November 2022) - Ruf, Matthias; Steeb, Holger
Abstract: Many physical processes in the field of rock physics are influenced by the presence of fractures and microcracks. Therefore, intact rock samples are often used for reproducible experimental studies, and cracks are artificially created by various methods. For this, one possibility is the use of thermal treatments. In this work, twelve different thermal treatments are experimentally studied for dry Bianco Carrara marble under ambient conditions. The focus is primarily on the influence of the cooling rate (slow versus fast cooling) in combination with different applied maximum temperatures. This also raises the question of the influence of the specimen size, which has never been systematically investigated in this context before. Therefore, three sizes of cylindrical core samples are investigated to identify a potential specimen size effect. As effective quantities on the core-scale, the bulk volume, the bulk density, and the P- and S-wave velocities, including shear wave splitting, are examined. To obtain a three-dimensional insight into the mechanisms occurring on the micro-scale level, micro X-ray Computed Tomography ( μ XRCT) imaging is employed. For both cooling conditions, with increasing maximum temperature, the bulk volume increases, the propagation velocities significantly drop, and shear wave splitting increases. This behavior is amplified for fast cooling. The bulk volume increase is related to the initiated crack volume as μ XRCT shows. Based on comprehensive measurements, a logarithmic relationship between the relative bulk volume change and the relative change of the ultrasound velocities can be observed. Although there is a size effect for fast cooling, the relationship found is independent of the specimen size. Also the cooling protocol has almost no influence. A model is derived which predicts the relative change of the ultrasound velocities depending on the initiated relative bulk volume change. Highlights: Thermal treatments of Carrara marble lead to significant bulk volume increase correlating with the initiated crack volume. High cooling rate systematically amplifies the observable results of slow cooling. Thermally created cracks can initiate or amplify shear wave splitting. The specimen size affects the resulting acoustic velocities for a high cooling rate. Independent of the cooling rate and specimen size, the relative bulk volume change is a suitable parameter to predict the acoustic velocities.